Leflunomide as a potential second-line drug in the treatment of sarcoidosis - A. A. Vizel; I. Yu. Vizel (Туберкулез и болезни лёгких, 2019)
Sarcoidosis is systemic granulomatosis of an unknown nature, the course of which varies from spontaneous remission to progression resulting in failure of organs and systems. The article presents a review of current approaches to treatment of sarcoidosis putting special emphasis on the use of the anti-rheumatic drug of leflunomide (LEF). LEF is a prodrug derived from isoxazole, which is rapidly converted by liver and intestinal wall into an active metabolite, A77-1726, which inhibits the biosynthesis of pyrimidine nucleotides. LEF slows down the cell cycle, inhibits the activity of the mitochondrial enzyme dihydroorotate dehydrogenase, a key enzyme in the primary (de novo) synthesis of pyrimidines used by lymphocytes for clonal expansion. There are English reports on 2 retrospective studies of LEF used to manage sarcoidosis refractory to traditional therapy and a number of descriptions of clinical cases that provided encouraging results. LEF was found to be safer than methotrexate with comparable efficacy in both rheumatoid arthritis and sarcoidosis. Literature data indicate the feasibility of studying leflunomide in clinical practice of sarcoidosis.